Sleep and movement disorders - Chokroverty, Sudhansu; Hening, Wayne A; Walters, Arthur S (Butterworth-Heinemann, 2003)
This unique text brings together two often interconnected areas, sleep disorders and movement disorders, to provide sleep specialists, experts on movement disorders, and general neurologists with practical, interdisciplinary guidance on evaluation and treatment. It reviews new findings, based on animal models, genetic studies and imaging, that have led to a deeper understanding of the clinical features, epidemiology, and pathogenesis of these disorders. Readers will find the latest information on the association of Parkinson\'s disease, Tourette\'s syndrome, and other movement disorders with prominent sleep complaints and a higher incidence of sleep disorders, as well as the profound influence of sleep on the motor system, which amounts to a reorganization of motor control.
Keywords: Sleep; spánek; Sleep Wake Disorders; syndromy spánkové apnoe; neurologie; pohybové poruchy; Movement Disorders; poruchy spánku a bdění; Sleep Apnea Syndromes